2005
DOI: 10.1016/j.ijid.2004.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculous brain abscess in AIDS patients: report of three cases and literature review

Abstract: Tuberculous brain abscess must be considered in the differential diagnosis of intracranial mass in AIDS patients. A careful epidemiological, clinical and laboratory evaluation may guide a diagnostic suspicion. Surgery combined with specific anti-tuberculosis treatment seems to determine a good outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 26 publications
(28 reference statements)
0
29
0
4
Order By: Relevance
“…While, focal forms of cerebral tuberculosis (tuberculoma and, less likely tuberculous brain abscess) allow for differential diagnosis of CT mainly in developing countries (Trujillo et al, 2005). Primary CNS lymphoma usually presents with a CD4 count of less than 50 cells/cumm, CT occurs below 100 cells/cumm, and cerebral TB is more frequently present with a CD4 count above 200 cells/cumm (Vidal et al, 2004a;Vidal et al, 2005a;Vidal et al, 2005b). In addition to these more common neurological diseases, the differential diagnosis of CT includes other opportunistic infections such as progressive multifocal leucoencephalopathy, herpes simplex encephalitis, and cryptococcal meningitis; AIDS-and non-AIDS-associated tumors such as metastases of disseminated lymphoma and glioblastoma multiforme, respectively; and vascular diseases.…”
Section: Diagnostic Approaches -From Conventional To Advanced Technologymentioning
confidence: 99%
“…While, focal forms of cerebral tuberculosis (tuberculoma and, less likely tuberculous brain abscess) allow for differential diagnosis of CT mainly in developing countries (Trujillo et al, 2005). Primary CNS lymphoma usually presents with a CD4 count of less than 50 cells/cumm, CT occurs below 100 cells/cumm, and cerebral TB is more frequently present with a CD4 count above 200 cells/cumm (Vidal et al, 2004a;Vidal et al, 2005a;Vidal et al, 2005b). In addition to these more common neurological diseases, the differential diagnosis of CT includes other opportunistic infections such as progressive multifocal leucoencephalopathy, herpes simplex encephalitis, and cryptococcal meningitis; AIDS-and non-AIDS-associated tumors such as metastases of disseminated lymphoma and glioblastoma multiforme, respectively; and vascular diseases.…”
Section: Diagnostic Approaches -From Conventional To Advanced Technologymentioning
confidence: 99%
“…The incidence of intracerebral tuberculomas in patients with HIV ranges from 1-10%; in these patients, cerebral abscesses are much less frequent. Vidal JE et al [5] reported three cases of tuberculous brain abscess in AIDS patients and reviewed nine similar cases. Excepting one, all patients had single lesion in CT scan.…”
Section: Discussionmentioning
confidence: 99%
“…Kyusik Kang · Ilhan Lim · Jae-Kyu Roh become more prevalent during the last 20 years owing to the advent of human immunodefi ciency virus (HIV) [1]. Uncommonly, cerebral disease resulting from Mycobacterium tuberculosis appears as a tuberculoma and rarely as a tuberculous brain abscess [1].…”
Section: Positron Emission Tomographic Fi Ndings In a Tuberculous Bramentioning
confidence: 99%